Deep desulfurization of kerosene by electrochemical oxidation and extraction in Mn2+/Mn3+ electrolyte. (3rd April 2018) - Tang, Xiao-dong; Jiao, Shuang; Li, Jing-jing; Hu, Na
ABSTRACT: In this paper, choosing the mixed solution of MnSO4 solution and H2 SO4 as electrolyte, with the progressing of electrolysis reaction, Mn 3+ was generated as intermediate product, combining with water to produce the oxidation agent MnOOH, which was easy to oxidize the sulfur compounds to generate sulfoxide or sulfone. At the optimal electrochemical oxidation desulfurization conditions, the sulfur content of kerosene decreased from 180 µg/g to 8.87 µg/g and the desulfurization efficiency reached to 95.07%. And the cycle of electrolyte and mechanism of electrochemical oxidation desulfurization has been discussed.